Presence of Antibodies Against Mycoplasma penetrans in Patients with Antiphospholipid Syndrome - Herrera-Saldivar, Elizabeth; Yanez, Antonio; Banuelos, David; Gil, Constantino; Cedillo, Lilia (IntechOpen, 2012)
None